2016
DOI: 10.1103/physrevb.93.165143
|View full text |Cite
|
Sign up to set email alerts
|

Role of spin fluctuations in the conductivity ofCrO2

Abstract: We present a time-resolved terahertz spectroscopic study of the half-metallic ferromagnet CrO 2 .The ultrafast conductivity dynamics excited by an optical pump displays a very short (several picoseconds) and a very long (several hundred picoseconds) characteristic time scales. We attribute the former to the electron-phonon relaxation and the latter to the spin-lattice relaxation. We use this distinction to quantify the relative contribution of the scattering by spin fluctuations to the resistivity of CrO 2 : w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 42 publications
1
8
0
Order By: Relevance
“…The monopolar (spherically symmetric) piece of the second-order field equation (42) contains several dissipative terms, including a term equal to the flux of energy at infinity, a term equal to the flux of energy through the horizon, and a term describing the rate of orbital-energy dissipation (note that all these quantities are, in fact, second order in η). It can be analytically shown that this portion of the field equation precisely yields the balance law (77). This result, yet to be published, was derived by one of us (AP) recently.…”
Section: Balance Laws and Adiabatic Evolutionmentioning
confidence: 77%
See 3 more Smart Citations
“…The monopolar (spherically symmetric) piece of the second-order field equation (42) contains several dissipative terms, including a term equal to the flux of energy at infinity, a term equal to the flux of energy through the horizon, and a term describing the rate of orbital-energy dissipation (note that all these quantities are, in fact, second order in η). It can be analytically shown that this portion of the field equation precisely yields the balance law (77). This result, yet to be published, was derived by one of us (AP) recently.…”
Section: Balance Laws and Adiabatic Evolutionmentioning
confidence: 77%
“…This means one normally has to compute a large number of -modes ( max ∼ 50 is typical), which can become computationally expensive. This problem can be mitigated through the use of "high-order regularization parameters", which analytically capture some of the higher-order terms in the 1/ expansion of F α S (z) [76,77]; these higher-order terms can be constructed such that they sum to zero, but including them accelerates the rate of convergence. For more details, refer to [26,27].…”
Section: Mode-sum Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…60,61 Its rutile crystal structure and previously measured bulk electronic structure 61 are somewhat encouraging for our purposes. Additionally, synthesis of thin film CrO 2 has also been reported.…”
Section: B Spin Polarized Junctionsmentioning
confidence: 80%